2009
DOI: 10.1080/09638280802273473
|View full text |Cite
|
Sign up to set email alerts
|

How does exercise influence fatigue in people with multiple sclerosis?

Abstract: This study details the positive and negative influences of exercise on fatigue perceptions in people with MS. Healthcare professionals therefore, need to be cognisant of strategies which may enhance 'perceived control over fatigue' and promote 'listening to your body', in order to maximise the benefits of exercise intervention for individuals with MS-related fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
131
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(137 citation statements)
references
References 20 publications
3
131
1
2
Order By: Relevance
“…We can suppose, as other studies suggested [33,34], that better perceived physical improvements in strength and balance due to individualized neuromotor strategies can reduce the fatigue experience.…”
Section: Discussionmentioning
confidence: 94%
“…We can suppose, as other studies suggested [33,34], that better perceived physical improvements in strength and balance due to individualized neuromotor strategies can reduce the fatigue experience.…”
Section: Discussionmentioning
confidence: 94%
“…Regular physical activity has been recognized as one of the most consistent positive interventions in patients with MS [10], resulting in improved cardiovascular function, muscular strength and the delayed onset of fatigue [11]. Ironically, acute exercise itself has been suggested to lead to a worsening of symptoms, reduced activity [12], and chronic inflammation [13].…”
Section: Introductionmentioning
confidence: 99%
“…13 However, past evidence is unclear as to whether exercise may increase symptoms (ie, pain or fatigue) immediately following exercise in those with MS and CFS. 2,[9][10][11] Indeed, concern about a detrimental effect of exercise may deter people with these diseases from undertaking exercise, despite the absence of strong quantitative evidence that exercise may negatively affect symptoms over a longer period of time. In this study investigating the immediate effect of exercise on people with MS and CFS, we hypothesized that undertaking a 15-minute bout of aerobic exercise would increase pain and fatigue and decrease function for up to 24 hours following exercise.…”
Section: Participantsmentioning
confidence: 99%
“…In contrast, Mostert and Kesselring 8 reported an immediate negative effect following cycling in people with MS, with increased muscle spasms. Qualitative evidence in studies of MS suggests that fatigue [9][10][11] and muscle pain 9 may result the day after exercise.…”
Section: Participantsmentioning
confidence: 99%